2020
DOI: 10.3389/fgene.2020.00603
|View full text |Cite
|
Sign up to set email alerts
|

Causal Effects of Overall and Abdominal Obesity on Insulin Resistance and the Risk of Type 2 Diabetes Mellitus: A Two-Sample Mendelian Randomization Study

Abstract: Overall and abdominal obesity were significantly associated with insulin resistance and type 2 diabetes mellitus (T2DM) risk in observational studies, though these associations cannot avoid the bias induced by confounding effects and reverse causation. This study aimed to test whether these associations are causal, and it compared the causal effects of overall and abdominal obesity on T2DM risk and glycemic traits by using a two-sample Mendelian randomization (MR) design. Based on summary-level statistics from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 49 publications
1
27
1
Order By: Relevance
“…The INS locus is complex, and how these polymorphisms affect insulin secretion remain unclear, but are beginning to be investigated. Mendelian randomization studies support a causal role for genetically driven glucose-stimulated hyperinsulinemia in obesity [ 98 ], although studies also support a causal contribution of BMI to fasting insulin and insulin resistance [ 99 ]. It is likely that there is bi-directional causality and the results depend on which single-nucleotide polymorphisms and which anthropomorphic traits are chosen for analysis.…”
Section: Hyperinsulinemia Plays a Causal Role In Obesitymentioning
confidence: 99%
“…The INS locus is complex, and how these polymorphisms affect insulin secretion remain unclear, but are beginning to be investigated. Mendelian randomization studies support a causal role for genetically driven glucose-stimulated hyperinsulinemia in obesity [ 98 ], although studies also support a causal contribution of BMI to fasting insulin and insulin resistance [ 99 ]. It is likely that there is bi-directional causality and the results depend on which single-nucleotide polymorphisms and which anthropomorphic traits are chosen for analysis.…”
Section: Hyperinsulinemia Plays a Causal Role In Obesitymentioning
confidence: 99%
“…Finally, because of the observational design of the studies, residual confounding cannot be excluded and should be considered when interpreting the results. Recent mendelian randomisation studies, however, suggested a casual effect of general and central adiposity on the risk of type 2 diabetes 5556…”
Section: Discussionmentioning
confidence: 99%
“…Recent mendelian randomisation studies, however, suggested a casual effect of general and central adiposity on the risk of type 2 diabetes. 55 56 …”
Section: Discussionmentioning
confidence: 99%
“…In a recent paper, it was suggested that the body mass index (BMI), which is the most used index in clinical practice, could be considered a useful clinical threshold to help the decision [ 4 ]. However, BMI does not discriminate fat mass from fat-free mass, or the percentage of fat mass and its distribution, which in turn are considered the most important predictors of cardio-metabolic risk [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%